When we must forget: the effect of cognitive load on prospective memory commission errors. Issue 3 (15th March 2020) - Matos, Patrícia; Santos, Flávia H.; Albuquerque, Pedro B.
ABSTRACT: Recent studies consistently show that prospective memory (PM) intentions are not always deactivated when no-longer needed and might be erroneously performed upon encountering the once relevant cue – termed PM commission errors. However, empirical evidence on the potential mechanisms that might lead to this kind of memory failure remains mostly unexplored. This study aimed to investigate the influence of the ongoing task demands on PM deactivation of non-performed intentions. Younger adults, except for those in the no-PM condition, were asked to perform a PM task and were then told that the intention was finished. Later, they perform a lexical decision task with some trials containing (irrelevant) PM cues while simultaneously carrying out a counting recall task with two levels of difficulty. The results showed a higher risk of PM commission errors under moderate cognitive load (74%) as compared to the no-load condition (40%). Results also show that commission error risk did not increase in the high-load (54%) compared with the moderate-load condition. Furthermore, comparisons of the ongoign task performance between the no-PM condition and the other conditions with a PM task requirement support that commission errors might arise from a spontaneous PM retrieval. The implications of these findings are discussed within the dual-mechanisms account.